Virginia Woolf, the intellectual, and the public sphere - Cuddy-Keane, Melba (Cambridge University Press, 2003)
Melba Cuddy-Keane relates Woolf's literary reviews and essays to early twentieth-century debates about the value of "highbrow" culture; the methods of instruction in universities and adult education; and the importance of an educated public for the realization of democratic goals. Combining a wealth of historical detail with a penetrating analysis of Woolf's essays, this study will alter our views of Woolf, modernism, and intellectual endeavor.